Letter from S.G. Tipton to Jane Tolmach - S.G. Tipton:::::: (1960)
A letter from S.G. Tipton to Jane Tolmach in which Tolmach is elected as a delegate for the Democratic National Convention. She is free to join the Flying Donkey Club with her own key.